1995
DOI: 10.1021/ma00108a043
|View full text |Cite
|
Sign up to set email alerts
|

Phase Transitions in Swollen Networks

Abstract: Equilibrium swelling of networks capable of separating into a highly swollen and a collapsed phase is discussed on the basis of a concentration-dependent pair interaction parameter. Classic rules, to be obeyed by the various binodals and their metastable and unstable extensions, rationalize the experimentally accessible portions of the phase diagram and are covered by a simple model yielding acceptable parameter values when fitted to swelling data on the system water/polyW-isopropylacrylamide). The description… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
111
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(116 citation statements)
references
References 8 publications
3
111
1
Order By: Relevance
“…20 However, for polymer gels that undergo discontinuous volume phase transitions, the threephase equilibrium among the pure solvent, the swollen gel, and the collapsed gel requires a stronger quadratic dependence of = 0 + 1 + 2 2 to describe such systems. 19 Experimentally Horkay and co-workers 9,27 found that a that was independent of the polymer concentration could not adequately describe the osmotic pressure data of polyacrylate gels, but that a that was linearly dependent on provided a satisfactory model for these gels.…”
Section: +mentioning
confidence: 99%
“…20 However, for polymer gels that undergo discontinuous volume phase transitions, the threephase equilibrium among the pure solvent, the swollen gel, and the collapsed gel requires a stronger quadratic dependence of = 0 + 1 + 2 2 to describe such systems. 19 Experimentally Horkay and co-workers 9,27 found that a that was independent of the polymer concentration could not adequately describe the osmotic pressure data of polyacrylate gels, but that a that was linearly dependent on provided a satisfactory model for these gels.…”
Section: +mentioning
confidence: 99%
“…To an ice-cold solution of glycine ethyl ester, Marchetti et al 18 20 suggested a simple model in manner. The mixture was stirred at room temperwhich the polymer-solvent interaction parameature for 5 h. The precipitated solid (Et 3 NHCl), ter depends not only on the temperature but also which was gradually separated during the reacon the concentration of polymer and fitted it to tion, was filtered off, and the filtrate was evapoInomata's swelling data.…”
Section: Methodsmentioning
confidence: 99%
“…dissolved solution was held in a thermostated waThe elastic contribution, DG el , is expressed as ter bath at 70ЊC. The reaction was initiated by follows 20,23 : adding 200 mL of 1 wt % solution of APS. Simultaneously, 100 mL of 1 wt % solution of Tween20 to DG el prevent aggregation during polymerization.…”
Section: Theoretical Considerationmentioning
confidence: 99%
“…À30 1C) and vitrification is likely to have no effect on the crystallization of water. 15,16 In noncrystallizable solutions, water is assumed to be bound to polymer chains and a polymer/solvent complex forms. It remains unclear whether this complex is kinetically or thermodynamically controlled.…”
Section: Introductionmentioning
confidence: 99%